Absenteeism of nursing in a university hospital of Pernambuco state - Edeilson Vicente Ferreira; Maria José Dantas Mesquita de Amorim; Renata Maria Cavalcanti Lemos; Nadja da Silva Ferreira; Flávio de Oliveira Silva; José Rodrigues Laureano Filho (Rev Rene)
Absenteeism in nursing is an issue of serious concern since it interferes on client care besides overwhelming the other team members and may even lead to illness. The objective of this work was to identify and analyze the causes of absenteeism of hospital nursing service through an audit of records of unscheduled absences. This exploratory study with a quantitative approach was conducted in the Nursing Department in December 2010. The sample was composed by the registration forms from the period of January to December 2009. We analyzed data on gender and the most common causes of absenteeism. It was found out the prevalence of absenteeism in women, 72.86%, being the most common causes of sick leave, those related to the musculoskeletal system (20.63%). It was concluded that it was necessary to adopt preventive measures and programs aimed at improvements in working conditions favoring a better quality of life for health professionals and a dignified nursing care to users.